2004
DOI: 10.1079/rafs200485
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the effectiveness of technology transfer for conservation cropping systems through research and field design

Abstract: A survey was conducted in 2002 to measure the success of technology transfered to growers (i.e., changes in attitudes and behaviors) from a long-term, large-scale, integrated cropping systems experiment called the Ralston Project, near Ralston, Washington, USA. Non-irrigated, cereal and oilseed growers who participated in biennial field tours (1996–2000) were mailed a self-administered questionnaire, which asked about: (1) their interest, use and adoption of technology developed or demonstrated in the project;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The four cropping systems evaluated included (i) reduced-tillage WWF, (ii) SWChF, (3) CHRSW, and (4) HRSWSB. The specific cropping systems, field operations, and technologies used were a compromise between growers' needs and interest and scientists' interests expressed during preliminary planning meetings (Forté-Gardner et al, 2004). Attendees decided mutually to grow only spring cereal grains in this study as alternative systems because both fall and spring broadleaf crops seldom were grown in this region, and very little information was available on the production of spring cereals generally and no-till specifically.…”
Section: Cropping Systems Cultivars and Field Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The four cropping systems evaluated included (i) reduced-tillage WWF, (ii) SWChF, (3) CHRSW, and (4) HRSWSB. The specific cropping systems, field operations, and technologies used were a compromise between growers' needs and interest and scientists' interests expressed during preliminary planning meetings (Forté-Gardner et al, 2004). Attendees decided mutually to grow only spring cereal grains in this study as alternative systems because both fall and spring broadleaf crops seldom were grown in this region, and very little information was available on the production of spring cereals generally and no-till specifically.…”
Section: Cropping Systems Cultivars and Field Proceduresmentioning
confidence: 99%
“…In the spring/summer of 1995, scientists from the USDA-ARS and Washington State University (WSU) met with regional wheat growers to discuss the low-rainfall crop production problems in general and spring crop production problems specifically (Forté-Gardner et al, 2004). The major problem confronting both growers and researchers was the lack of agronomic and economic information for optimum spring crop production practices.…”
mentioning
confidence: 99%
“…The desire for greater scale, relevance and collaboration in research and adoption is not unique to Australian farmers. A survey of growers associated with a large, long-term conservation farming experiment in Washington State, USA, found that they valued the Project's 'whole-system' approach as well as its larger, commercial-scaled plots, and the collaboration that took place between the growers and scientists (Forté-Gardner et al 2004). Ensuring that a range of stakeholders work closely with scientists has also been found to be successful with land use studies, including soil and water studies in the Netherlands, where Bouma et al (2008) found that exploring the needs of land managers led not only to innovative ideas but also to greater commitment of collaborators and better definition of the areas of research to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Growers were more inclined to relate with peers or innovators to seek ideas to develop and adopt conservation technology than other communication processes. This suggests the importance to identify opinion leaders among growers and enhance their roles in the adoption process (Carlson and Dillman 1999;Forté-Gardner et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Several surveys were conducted by STEEP projects that provided perspectives on grower attitudes and behavior regarding aspects of conservation farming (Carlson and Dillman 1999;Forté-Gardner et al 2004). These also served as predictors of relative changes in the use of conservation practices.…”
Section: Methodsmentioning
confidence: 99%